Impacts of improved biomass cookstoves on child and adult health: Experimental evidence from rural Ethiopia. (April 2021) - LaFave, Daniel; Beyene, Abebe Damte; Bluffstone, Randall; Dissanayake, Sahan T.M.; Gebreegziabher, Zenebe; Mekonnen, Alemu; Toman, Michael
Highlights: A randomly distributed, improved biomass cookstove improved child growth by 0.3–0.4 standard deviations after 3 years. The positive effect holds only for children exposed to the improved stove during their first 3 years of life. We find no impact on the health outcomes of older children or adults. Indoor fine particulate measures (PM2.5 ) remain well above WHO standards yet correlate with the observed health impacts. Abstract: We present the three-year impacts of an improved biomass cookstove on child and adult health in rural Ethiopia. The Mirt stove is designed to cook injera, the staple bread of Ethiopia estimated to consume 60 percent of household cooking energy and about half of all energy in the country. Though it would not be considered a fully "clean" cooking technology and is not used on a daily basis, Mirt's documented fuelwood reduction potential and application to the highly energy-intensive baking of injera raises the question of whether it might offer health benefits to users. After near complete stove adoption during an initial one-year randomized controlled trial, 60 percent of treatment households continued to use the improved stoves three-years on and experience moderate reductions in hazardous airborne particulate matter. In a pre-specified analysis, we find treatment status is associated with a precisely estimated 0.3–0.4 standard deviation improvement in height-for-age of young children exposed to the stoves during their first years of life–a substantial effect with implications for greater health and well-being throughout the life course. This association notwithstanding, we find no changes in the respiratory symptoms or physical functioning of older children and adult cooks. Measures of fine particulate matter taken within study households remain over an order of magnitude higher than WHO standards, but follow a statistically significant gradient with respect to the observed height-for-age improvements. The results advance understanding of the health impacts of hazardous air pollution while also refining design and implementation options for interventions geared toward improving well-being in similar environments.